Mott‐Schottky Electrocatalyst: Spontaneously Formed Mott‐Schottky Electrocatalyst for Lithium‐Sulfur Batteries (Adv. Mater. Interfaces 22/2020). Issue 22 (20th November 2020) - Wang, Yuankun; Zhang, Ruifang; Sun, Zehui; Wu, Hu; Lu, Shiyao; Wang, Jianan; Yu, Wei; Liu, Jiamei; Gao, Guoxin; Ding, Shujiang
Abstract : Enhancing the catalytic activity of electrocatalyst in lithium sulfur electrochemistry by a facile method is important and challenging. In article number 1902092, Guoxin Gao, Shujiang Ding, and co‐workers propose a spontaneous oxidation strategy to build Mott‐Schottky electrocatalyst in lithium sulfur batteries. The redistributed electron at heterogenous interface results in fast polysulfide redox, thus advanced lithium sulfur batteries with superior performance are achieved.